Neuroendocrine neoplasms: Evolving and future treatments. (August 2021) - Spyroglou, Ariadni; Bramis, Konstantinos; Alexandraki, Krystallenia I.
Abstract: Neuroendocrine neoplasms (NENs) are relatively rare neoplasms. Most NENs are slowly progressing malignancies with prolonged survival even in the presence of advanced metastatic disease, implying an increased need for additional therapies on failure of those initially administered. However, a subset of NENs may display truly aggressive behavior, often refractory to current chemotherapeutic regimens, underlining the need for more appropriate schemes. Following these unmet needs, new therapies are emerging based on advances of NEN pathogenesis, along with modifications of those previously used to improve their efficacy. Long-acting somatostatin analogs also in above-label doses, molecular and peptide receptor radionuclide targeted treatments, chemotherapy, and immunotherapy are available options, but their appropriate sequence is still to be defined, and the choice of monotherapy or combination therapy should be individualized. Advances in the molecular pathogenesis of NENs and larger prospective studies will shed light on biomolecular tumor markers, suggesting the appropriate sequence of treatment in individual patients. Highlights: Besides from the clear recommendation for SA usage in advanced epNETs, newly introduced above-label doses of SAs present a further option in progressive neoplasms. The combination of immune checkpoint inhibitors with further established treatments (SAs, temozolomide) shows promising results and will be further investigated. The appropriate sequence of NEN therapies has not been clarified so far, but prognostic factors predicting the biological behaviour of NENs will allow a personalized treatment approach.